Public transportation modelling of UP Diliman campus using VISSIM - Reynales, John Paul M.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
A traffic simulation model of UP Diliman using the VISSIM platform is being developed for the past few years. In developing the model, six processes were proposed - the development of road networks, establishment of parking lots, modeling of public transportation parameters, modeling of pedestrian behavior parameters, calibration of vehicle and driver behavior parameters and lastly, network validation. The study aims to further develop the model by adding public transport components, and to test the updated model by applying a case study. The model already has an established road network and parking lot zones prior to the start of this study. In modeling the campus' public transportation parameters, two major factors are needed - the location of public transport stops and routes of all public transport vehicles. A total of 72 public transport stops and 6 public transport routes were created to update the current VISSIM model. Arrival and dwell times of public transport vehicles were based from the conducted Jeepney Stop Surveys. The number of boarding passengers per public transport stop was based from Boarding and Alighting Surveys, conducted in collaboration with other researchers. A case study was made by comparing the average dwell times and queue times for the base case and for cases wherein the hourly vehicle arrival is increased. Also, an assessment of ICE Toki stop was made. Based from the simulations, it was observed that the average dwell times decrease as the hourly vehicle arrival increase. The optimum vehicle arrival rate for the case study is four times the current rate, or 168 vehicles per hour. This is the rate at which average dwell times and queue times are both minimal. For the ICE Toki stop assessment, an average of 9 vehicles per hour having an average dwell time of 25.58 s is observed. This corresponds to an average waiting time of 185.58 seconds, which is normal for jeepney stops along UP - Toki route.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- University of the Philippines; Traffic flow -- Simulation methods